(untitled) (Journal of the Management Sciences, 2025)
As Nigeria continues to emerge as Africa’s fintech epicenter, fintech firms face both growth opportunities and sustainability challenges. The study adopts a quantitative descriptive research design, utilizing secondary data from audited financial reports, regulatory sources, and ESG disclosures between 2022 and 2024. Key performance indicators analyzed include revenue growth, transaction volume, agent network coverage, and ESG compliance. Findings reveal that Moniepoint consistently ranked among the top three fintech firms in Nigeria, in terms of financial metrics (revenue growth rates, network, and active agents). In terms of sustainability, Moniepoint has demonstrated progress in environmental efficiency, gender inclusion, and governance transparency, ranking second among peers in ESG disclosure. The research concludes that Moniepoint has some competitive advantages. This study offers valuable insights for fintech operators, investors, and policymakers on sustainable digital finance models in emerging markets. It also contributes to the literature on ESG performance within Africa’s digital financial services industry.